PWE-111 Non invasive prediction of oesophageal varices based on transient elastography liver stiffness measurement. (22nd June 2015) - Mirza, NM; Akram, A; Sheikh, F; Koss, K
Abstract : Introduction: Transient elastography is a promising noninvasive method for assessing advanced fibrosis in patients with chronic liver disease and has a comparable sensitivity and specificity profile to liver biopsy. Variceal bleeding is the most serious complication of advanced liver disease and early recognition is of prime importance to prevent this life-threatening complication. In cirrhotic patients, liver stiffness measurements range from 12.5 to 75.5 kPa. However, the clinical relevance of these values is unknown. This study was carried out to investigate the reliability of predicting varices using transient elastography liver stiffness measurement. Method: 1500 patients had liver stiffness measurement (LSM) using transient elastography between January 2011–January 2015 at Macclesfield District General Hospital. Patients who had LSM >12 kPa and underwent gastroscopy were included in the study. Specificity, sensitivity, positive and negative predictive values were calculated for different cut off values of liver stiffness. Variable cut off values were also tested for different aetiologies. Results: 150 patients were included in the study; 80 males and 70 females. The most common aetiology was alcohol related liver disease (ARLD) representing 39%, followed by non-alcoholic fatty liver disease (NAFLD) 19% and viral hepatitis 11%. Age range of our cohort was 22–90 years (average 61.7). 27 patients (18%) had oesophageal varices. Mean liver stiffness measurement was much higher (51.6 kPa) in the group with varices as compared to the group with no varices (31.9 kPa). LSM cut off value of 25 kPa showed sensitivity of 92.6% and specificity of 56.9% with positive predictive value of 32%. A lower cut off value of 21.5 kPa showed higher sensitivity (100%), but low positive predictive value of 30%. In our study no significant variations were observed between different aetiologies. Conclusion: Transient elastography is a useful non invasive method for assessing patients with chronic liver disease. It allows us to stratify the degree of liver fibrosis and also to predict the risk of developing oesophageal varices. Patients with advanced fibrosis/cirrhosis with low LSM < 21.5 kPa have a low risk of developing oesophageal varices and may avoid unnecessary endoscopy procedure. We recommend that all patients with LSM > 21.5 kPa should undergo surveillance endoscopy for oesophageal varices. Disclosure of interest: None Declared.